Assessing the Agreement of Light Microscopic Evaluation of Oral Lichen Planus Lesions With Associated Direct Immunofluorescence Evaluation - Blake T Hansen; Jeffrey B Payne; Kaeli K Samson; Peter J Giannini (SAGE Publishing, 2023)
Aim/objective: Assess agreement between light microscopy and direct immunofluorescence (DIF) for histopathologic evaluation of oral lichen planus (OLP). Methods: Records evaluated included 60 OLP, 16 lichenoid mucositis (LM), and 56 non-OLP/non-LM cases. Cases had both light microscopic and DIF evaluations. Histopathologic parameters of OLP included: (1) hydropic degeneration of the basal cell layer, (2) band-like lymphocytic infiltrate immediately subjacent to the epithelium, and (3) presence of Civatte bodies. Two calibrated examiners independently assessed light microscopic features. Examiners reviewed cases with discordant diagnoses to determine a consensus diagnosis. Intra-rater reliability (IRR), sensitivity, specificity, positive, and negative predictive values (PPV and NPV) were determined. Results: Of 132 patients, 72.7% were female, average age 61.9 (SD = 13.8). Most common sites were gingiva (37.9%), buccal mucosa (37.1%), and tongue (7.6%). IRR was 0.74 (95% CI: 0.40, 1.00) for the consensus diagnosis and 0.73 (95% CI: 0.39, 1.00) and 0.34 (95% CI: −0.03, 0.72) for the 2 examiners. Comparing consensus and definitive diagnoses: sensitivity of light microscopy: 0.32 (95% CI: 0.20, 0.45); specificity: 0.88 (95% CI: 0.78, 0.94); PPV: 0.68 (95% CI: 0.48, 0.84), and NPV: 0.61 (95% CI: 0.51, 0.70). Conclusion: Light microscopy alone is not a viable alternative to adjunctive DIF for diagnosis of OLP lesions.